Organoid models: applications and research advances in colorectal cancer - Wu, Yijie; Sha, Yu; Guo, Xingpo; Gao, Ling; Huang, Jian; Liu, Song-Bai (Frontiers in Oncology, 2025)
This review summarizes the applications and research progress of organoid models in colorectal cancer research. First, the high incidence and mortality rates of colorectal cancer are introduced, emphasizing the importance of organoids as a research model. Second, this review provides a detailed introduction to the concept, biological properties, and applications of organoids, including their strengths in mimicking the structural and functional aspects of organs. This article further analyzes the applications of adult stem cell-derived and pluripotent stem cell-derived organoids in colorectal cancer research and discusses advancements in organoids for basic research, drug research and development, personalized treatment evaluation and prediction, and regenerative medicine. Finally, this review summarizes the prospects for applying organoid technology in colorectal cancer research, emphasizing its significant value in improving patient survival rates. In conclusion, this review systematically explains the applications of organoids in colorectal cancer research, highlighting their tremendous potential and promising prospects in basic research, drug research and development, personalized treatment evaluation and prediction, and regenerative medicine.